Analysis of the Innovations Diffusion Theory in Social Commerce - Sugangga, Rayyan; Puji Handayati; Arief Noviarakhman Zagladi (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
The skyrocketing of users and the number of transactions on TikTok Shop, illustrates the alignment of the results of an innovation process with the theory of innovation diffusion. However, it turned out to be not fully aligned due to the non-fulfillment of compatibility characteristics that made TikTok Shop currently stop operating. This article is a case study research that aims to explore the obstacles faced by TikTok Shop as well as provide an overview of solutions in the form of adjusting the TikTok Shop business model.